2009
DOI: 10.4314/wajm.v28i2.48431
|View full text |Cite
|
Sign up to set email alerts
|

Deep Vein Thrombosis: Risk Factors and Prevention in Surgical Patients

Abstract: BACKGROUND: Deep vein thrombosis (DVT) is a cause of preventable morbidity and mortality in hospitalized surgical patients. The occurrence of the disease is related to presence of risk factors, which are related primarily to trauma, venous stasis and hyper-coagulability. DVT seems not to be taken seriously by many surgeons in Nigeria. This is despite comprehensive studies that show no real differences in racial demography of the disease. OBJECTIVE: To highlight the importance of physician awareness about DVT e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
3
1
Order By: Relevance
“…This is deserving of further study, particularly as the rate observed in our study among pregnant women is alarmingly high. Some prior research has documented a rate of VTE in pregnant women around five times more than in the non-pregnant,12 and around a 1%–2% DVT risk after Caesarean section,27 with a high risk in the postpartum period 1 6. Our study, however, was not able to identify any significant association between pregnancy or the postpartum period and DVT, although this possibly could be due to a lack of power, given the small number of pregnant women enrolled.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…This is deserving of further study, particularly as the rate observed in our study among pregnant women is alarmingly high. Some prior research has documented a rate of VTE in pregnant women around five times more than in the non-pregnant,12 and around a 1%–2% DVT risk after Caesarean section,27 with a high risk in the postpartum period 1 6. Our study, however, was not able to identify any significant association between pregnancy or the postpartum period and DVT, although this possibly could be due to a lack of power, given the small number of pregnant women enrolled.…”
Section: Discussioncontrasting
confidence: 75%
“…The annual incidence in adults worldwide of a first VTE is 1–2 events per 1000 patient years4 and approximately 1 per 1000 adult patients suffers a clinically diagnosable event 5. VTE appears more common in Europe and the USA than in Asia and Africa 6. VTE is associated with bed rest or immobility and affects patients hospitalised for both medical and surgical conditions 7 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients undergoing elective orthopaedic procedures, such as hip or knee arthroplasty are already at high risk for venous thromboembolism 825 . The American Academy of Orthopaedic Surgeons (AAOS) guidelines report that a history of VTE significantly increases the risk in patients undergoing elective arthroplasty, and several studies cite additional risk factors such as: middle or old age, trauma, body mass index (BMI), cholesterol, high-density lipoprotein, apolipoprotein A, malignancy, prolonged surgery or contraceptive use, hormone therapy and pregnancy in women [826][827][828] . The risk of DVT is also increased in patients undergoing spinal surgery.…”
Section: -Should a Patient With Active Lower Extremity Dvt Undergo An...mentioning
confidence: 99%